Assessment of quality of life in children with epilepsy in rural settings of South India: A cross sectional study - Mullazy Paramadam Srujana; Easwaran Vigneshwaran; Gandesiri Sangeeth Kumar; Kolisetty Jyoshna; Mantargi Md Jaffar Sadiq (Wolters Kluwer Medknow Publications, 2017)
Background: Epilepsy is the most common pediatric neurological disorder which alters the conscious, behavior, motor activity, and autonomy function leads to compromised quality of life (QoL) in children. Objective: The aim is to assess the QoL, and to evaluate the influence of demographic and clinical factors on QoL in children with epilepsy. Materials and Methods: This is a cross-sectional study conducted over 1 year from October 2013 to September 2014. Baseline demographic characteristics and other details were collected from patient case data and through a semi-structured interview during their recruitment into the present investigation. The child version of TNO-AZL Children's QoL questionnaire was administered by the trained research coordinator to collect data from and about the study subjects. Statistical Analysis: ANOVA and student t-test were performed for the statistical analysis. The data analysis was performed using Graph pad instat 3.0.10.0. Results: The educational status, socioeconomic status, and maternal education were the demographic characters that significantly affected the QoL of study subjects. Type of seizures, early childhood history of seizures, duration of therapy and duration of epilepsy were the most important clinical characteristics that could significantly affect the QoL of study subjects. Conclusion: Further QoL studies and interventional programs may be conducted to improve the QoL and to individualize management in rural resident children with epilepsy.